Perspektif Hukum : Kearifan Lokal Sarung Tenun Kota Samarinda Dalam Gempuran Industrialisasi Di Kalimantan Timur - Gilvina Grace Bulam Abram; Syarief Hidayatullah; Aulia Vivi Yulianingrum (Indonesian Journal of Law, 2024)
Samarinda woven sarongs symbolize local wisdom reflecting the cultural identity of East Kalimantan. This research explores the challenges and conservation efforts amidst industrialization and globalization. Analyzing initiatives such as the One Village One Product (OVOP) program and legal protections under the 1945 Constitution, the study unveils strategies to enhance competitiveness and promote local cultural values. Despite significant efforts, the Samarinda woven sarong industry faces issues like raw material supply and limited youth interest. A holistic approach involving government support, local communities, and youth education is crucial for sustainability and industry growth. In conclusion, Samarinda woven sarongs not only safeguard cultural heritage but also hold economic potential in the global market